Management of polytrauma patients in emergency department: An experience of a tertiary care health institution of northern India - Payal, Puri (Second Affiliated Hospital of Zhejiang University School of Medicine, 2013)
BACKGROUND: In a tertiary care institute of northern India, the emergency department receives an average of 6–7 patients with poly trauma every day. Of these patients, some come directly and many are referred from other hospitals from the region. Various problems are faced in the management of patients with poly trauma. This study aimed to elicit various complaints, suggestions and possible solutions in the management of patients with poly trauma. METHODS: A retrospective cross sectional study was done on 210 patients in the emergency OPD for a period of 2 months. All the records of the patients with poly trauma were studied and the problems during their management were measured against 6 predetermined steps (step I to step VI). RESULTS: In the younger generation, males were predominantly the primary victims of poly trauma injury, and road traffic accident was the major etiological factor. Injuries involving more than 2 specialties induced many problems during the management of patients with poly trauma. Of 210 patients we studied, 32 patients had problems at various steps and maximum problems in step III, i.e. co-ordination between various specialties in the management of patients with poly trauma. CONCLUSION: A proper poly trauma management team and a well defined standard operative procedure are the keys to effective management of patients with poly trauma by minimizing the problems encountered.